2019
DOI: 10.1115/1.4043947
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell Behavior by Hydrostatic Pressure

Abstract: Hydrostatic pressure (HP) regulates diverse cell behaviors including differentiation, migration, apoptosis, and proliferation. Abnormal HP is associated with pathologies including glaucoma and hypertensive fibrotic remodeling. In this review, recent advances in quantifying and predicting how cells respond to HP across several tissue systems are presented, including tissues of the brain, eye, vasculature and bladder, as well as articular cartilage. Finally, some promising directions on the study of cell behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 144 publications
1
37
0
Order By: Relevance
“…In contrast, some researchers reported reductions in cell viability under pressure, although the pressure applied was four times (4 kPa) that used in this study (30). Whether these discrepancies were due to the use of different species/cell types and/or methods is not known; however, a review of the various methods commonly used to apply hydrostatic pressure has shown differences in cell proliferation and viability due to cell type and amount loaded (38).…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, some researchers reported reductions in cell viability under pressure, although the pressure applied was four times (4 kPa) that used in this study (30). Whether these discrepancies were due to the use of different species/cell types and/or methods is not known; however, a review of the various methods commonly used to apply hydrostatic pressure has shown differences in cell proliferation and viability due to cell type and amount loaded (38).…”
Section: Discussionmentioning
confidence: 56%
“…Existing HP bioreactors have preliminarily incorporated techniques regarding different HP conditions on cartilage formation and cartilage, and researchers may focus on the regulation of cellular behavior in HP research in the future. Further specific review of the role of hydrostatic forces in regulating cell behavior was provided by Liu et al [ 55 ].…”
Section: Considerations For Seeded Cells In Bioreactor Designmentioning
confidence: 99%
“…This complete fluid environment (defined here as "full vessel" for ease of reference) affects oxygen diffusion and hydrostatic loading, which fundamentally regulate homeostasis, [40][41][42] embryonic development [43][44][45] and key cellular processes such as differentiation, migration and proliferation. [46][47][48] Rotation of a culture vessel on clinostat, RPM or RWV devices induces fluid shear stresses and improves mass transport, which stimulate cell growth as in bioreactor culture. 49,50 Furthermore, simulated microgravity devices introduce system-specific artifacts that can affect cellular processes, such as centrifugal forces and vibrations (clinostats, RPMs, RWVs) 6 or magnetic fields (magnetic levitation devices) 51 but are seldom discussed.…”
Section: F I G U R Ementioning
confidence: 99%
“…Other than gravitational revectoring, s‐μg culture already presents a novel cellular environment compared to standard techniques in that the culture vessel must be completely filled with culture medium in order to reduce the effects of shear during rotationally‐mediated gravitational revectoring. This complete fluid environment (defined here as “full vessel” for ease of reference) affects oxygen diffusion and hydrostatic loading, which fundamentally regulate homeostasis, 40‐42 embryonic development 43‐45 and key cellular processes such as differentiation, migration and proliferation 46‐48 . Rotation of a culture vessel on clinostat, RPM or RWV devices induces fluid shear stresses and improves mass transport, which stimulate cell growth as in bioreactor culture 49,50 .…”
Section: Introductionmentioning
confidence: 99%